2018
DOI: 10.1016/j.neuroimage.2018.02.060
|View full text |Cite
|
Sign up to set email alerts
|

MIDAS: Regionally linear multivariate discriminative statistical mapping

Abstract: Statistical parametric maps formed via voxel-wise mass-univariate tests, such as the general linear model, are commonly used to test hypotheses about regionally specific effects in neuroimaging cross-sectional studies where each subject is represented by a single image. Despite being informative, these techniques remain limited as they ignore multivariate relationships in the data. Most importantly, the commonly employed local Gaussian smoothing, which is important for accounting for registration errors and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…To determine consistency in model performance between two separate sites, a comparison of regional volumetric patterns between sNMI groups was performed. For input, we used the RAVENS algorithm (Davatzikos et al, 2001) to produce gray and white matter tissue-density maps for each participant and applied voxelwise comparisons using MIDAS in which a regional volumetric profile is identified that maximally discriminates between groups (Varol et al, 2018). This comparison revealed that similar imaging patterns of brain maturation differentiated between those with high and low NMI scores, regardless of site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine consistency in model performance between two separate sites, a comparison of regional volumetric patterns between sNMI groups was performed. For input, we used the RAVENS algorithm (Davatzikos et al, 2001) to produce gray and white matter tissue-density maps for each participant and applied voxelwise comparisons using MIDAS in which a regional volumetric profile is identified that maximally discriminates between groups (Varol et al, 2018). This comparison revealed that similar imaging patterns of brain maturation differentiated between those with high and low NMI scores, regardless of site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…such that J = QY where Q is approximately invariant to permutation operations on Y . Assuming Y is zero mean, unit variance yields that E(J i ) = 0 and Var(J i ) = j Q 2 i,j under random permutations of Y [15,16]. Asymptotically this yields that J i → N (0, j Q 2 i,j ), which allows efficient statistical inference on the parameter values of J i .…”
Section: Methodsmentioning
confidence: 99%
“…bootstrapping/permutation testing) as there are numerous possible ways to integrate these different weights across searchlights (e.g. see MIDAS ( Varol et al , 2018 )). With increasing radius size, these issues make it nearly impossible to identify which voxels are most important for prediction, as accuracy scores are ‘smeared’ over spatial extents because searchlights are overlapping ( Viswanathan et al , 2012 ).…”
Section: Analytic Considerationsmentioning
confidence: 99%